Who Does the Shopping? German time-use evidence, 1996-2009 - Colin Vance; Vivien Procher (Transportation Research Record: Journal of the Transportation Research Board, 2013)
The labor force participation rate of women and men in industrialized countries is converging, but disparities in participation in unpaid activities nevertheless remain. Shopping for household maintenance is a time-consuming out-of-home activity that continues to be undertaken primarily by women, regardless of their employment status. The present study uses panel methods to analyze, descriptively and econometrically, gender disparities in shopping behavior of couples through the use of data from the German Mobility Panel for 1996 to 2009. Although women were still found to shop more than men, the evidence indicated that the differential narrowed in recent years, particularly in couples with children. Several individual and household characteristics were found to be significant determinants of shopping behavior, whereby employment status and children emerged to be the most important single factors. In addition, the possession of a driver's license, coupled with unrestricted car availability, increased the amount of time that each partner spent shopping.
Keywords: 330